Plant-Derived Antimicrobial Peptides as Potential Antiviral Agents in Systemic Viral Infections - Nour Mammari; Ysaline Krier; Quentin Albert; Marc Devocelle; Mihayl Varbanov; on behalf of the OEMONOM (MDPI AG, 2021)
Numerous studies have led to a better understanding of the mechanisms of action of viruses in systemic infections for the development of prevention strategies and very promising antiviral therapies. Viruses still remain one of the main causes of human diseases, mainly because the development of new vaccines is usually challenging and drug resistance has become an increasing concern in recent decades. Therefore, the development of potential antiviral agents remains crucial and is an unmet clinical need. One abundant source of potential therapeutic molecules are plants: they biosynthesize a myriad of compounds, including peptides which can have antimicrobial activity. Our objective is to summarize the literature on peptides with antiviral properties derived from plants and to identify key features of these peptides and their application in systemic viral infections. This literature review highlights studies including clinical trials which demonstrated that plant cyclotides have the ability to inhibit the growth of viruses causing human diseases, defensin-like peptides possess anti-HIV-1 activity, and lipid transfer proteins and some lectins exhibit a varied antimicrobial profile. To conclude, plant peptides remain interesting to explore in the context of emerging and re-emerging infectious diseases.